Dưới mắt tôi phê bình văn học Việt Nam hiện đại - Trương Chính 1916-2004 (Tủ sách phê bình văn học, 2016)
Nhất Linh, Khái Hưng, Nguyễn Công Hoan, Vũ Trọng Phụng, Lê Văn Trương, Trương Tửu, Thạch Lam, Lan Khai, Nguyễn Khắc Mẫn, Nguyên hồng, Song An Hoàng Ngọc Phách, Từ Ngọc